ANALISIS KEBUTUHAN RUANG TERBUKA HIJAU DALAM MENYERAP EMISI KARBON DIOKSIDA DI KOTA AMBON - Victor I. T. Malioy; Aryanto Boreel; Ronny Loppies (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
This study aims to determine the total carbon dioxide emissions produced by residents and motor vehicles, determine the total absorption capacity of carbon dioxide emissions, and determine the addition of Green Open Space (GOS) to absorb carbon dioxide emissions in Ambon city. This study uses data of land cover, population and number of motor vehicles in Ambon city in 2018. This study utilizes the use of GIS and is analyzed quantitatively. The results showed that the total carbon dioxide emissions produced by residents and motor vehicles were 393,295.56 tons / year. Ambon City has a total vegetation area of 29,679.25 ha or 82.57%. The total absorptive capacity of carbon dioxide emissions is 2,261,575.75 tons and is capable of absorbing carbon dioxide emissions of 1,868,280.20 tons, so that the requirement of green open space at both city and district scale is not necessary to add green open space because it is still sufficient to absorb carbon dioxide emissions.